(untitled) - Beschloss, Michael (New York, 2002)
Long before an Allied victory was assured during World War II, the Big Three--Roosevelt, Churchill, and Stalin--began discussing how to prevent Germany from ever again threatening the world. The fact that Germany today is a peaceful, democratic ally of the U.S. is "one of America's great twentieth-century international achievements," writes esteemed historian Michael Beschloss. How such a transformation was accomplished is the subject of The Conquerors.
Keywords: World war,Reconstruction,World war,United States; Diplomatic history,Foreign relations; 1939-1945,1939-1951,1939-1945,1933-1945; Germany,Germany